Scope and method of econometrics: illustrated by applications to American agriculture - Tintner, Gerhard (Statistical and Social Inquiry Society of Ireland, 1949)
Econometrics is the application of a specific method in the general field of economic science in an effort to achieve numerical results and to verify economic theorems. It consists in the application of mathematical economic theory and statistical procedures to economic data in order to establish numerical results in the field of economics.
Read before the Society, 21 March 1949
Keywords: Scope and method of econometrics; American agriculture; 314.15